Displacement resulting from disasters and crises and their impact on families and society A field study on a sample of heads of households in the city of Tobruk - Salma Abdullah Hamad Al-Shaeri; Ahmed Saleh Abdelrahman (Journal of Libyan Academy Bani Walid, 2025)
The study aims to identify some of the dimensions resulting from disasters and crises; their resulting effects on families and society; the material challenges facing families; and to reveal proposed community strategies to protect individuals and families from disasters and crises. The study is based on several questions: What are the dimensions, impacts, material challenges, and proposed community strategies to protect individuals and families from disasters and crises? The researchers relied on the use of the descriptive analytical approach, the questionnaire form tool, and a random sample of (120) respondents from heads of households in the city of Tobruk. Using the statistical method represented by simple tables consisting of frequencies and percentages, they reached a set of results, which are: 1.It demonstrated a range of dimensions (material, human, health, environmental, economic, social, and demographic) that occur after disasters and crises. It revealed a range of impacts resulting from disasters and crises on families and society. It highlighted the financial challenges facing families during disasters and crises. It outlined a range of proposed community strategies to protect individuals and families from disasters and crises.